A Comprehensive Study of Peshi Sharira w.s.r. to Urdhavashakhagata Peshi - Dudi, Sunita; Choudhary, Amit; Sharma, Manish Kumar; Sharma, Rakesh Kumar (International Research Journal of Ayurveda & Yoga, 2023)
Peshi are the compact form of Mamsa Dhatu having muscle fibres are arranged side by side and separated with each other. Peshi are lengthy and have fleshy appearance. Pitta Yukta Vayu enters the Mamsa and then divides it into Peshi. Peshi are component of body mainly composed of Mamsa Dhatu.Most of treatises provide the brief knowledge regarding the Peshi, but Acharya Sushruta mentioned more in details about the types, location, distribution, number and function of Peshi. The total number of Peshis enumerated is 500. Amongst these, 400 are located in Shakha, 66 in Koshtha and 34 in Greevapratyurdhwa. 100 Peshis of each upper limb divided under 8 regions and categorised under 12 Swaroopas. However, there is no specific identification of different Peshis based on Swaroopa, provided in the Samhita. Objective of this study is to study the literature on Peshi Shareera w.s.r. to Urdhavashakhagata Peshi in the light of modern science by cadaveric study and to categorise the Peshis of upper limbs into 12 Swaroopas. As per literary and cadaveric study, a total of 53 Peshis are found in the upper limb. 9 of 12 Swaroopa are found to be relevant for categorising the Urdhavashakha Peshis. The reason for the difference in the number of Peshis could be inclusion of tendons or aponeurosis, or single muscle observed in two or more regions or 2 heads of origin of a single muscle as two.